CREATING A CLOTHING COLLECTION USING KHANDASAVI AND GREEK PATTERNS FROM MODERN WOMEN'S OUTERWEAR - Boymatova Kamola Abdurakhmon qizi; Bakhtiyor Khamrakhojayev Yakhyokho'ovich; Sotvoldiyeva Nozima Khaydarjon qizi (Web of Journals Publishing, 2025)
This article studies the forms of modern women's outerwear, the analysis of the fabrics used, the physical, mechanical and operational properties of the materials, and as a result of these analyses, a new range of modern and complex-shaped dresses for women using national patterns was developed.
Keywords: Traditional clothing, pattern, grih, geometric, horde, tile.